Implementation and optimisation of alternative therapeutics for use in Clostridium sporogenes as a delivery vehicle - Budd, Patrick G. (2017)
Clostridium sporogenes is part of a highly diverse group of Gram positive, spore forming, anaerobic bacteria. C. sporogenes can be used as a delivery vehicle for chemotherapeutics in cancer treatment due to the inactive spore form of C. sporogenes only germinating in the microenvironment of the hypoxic tumour. Cancer, despite large investment in treatment and diagnosis, still remains one of the leading causes of death in the world. As such, improvements on current treatments are necessary to improve patient prognosis. Utilising C. sporogenes could be a cheap and effective way to do this by utilising their germination properties to deliver anti-cancer therapeutics directly to the hypoxic regions of solid tumours. Through introducing Prodrug Converting Enzymes (PCEs) into C. sporogenes when the spores germinate in the tumour the production of the PCE will result in the breakdown of a Prodrug into a toxic product resulting in an anti-cancer effect. This system is known as Clostridial Directed Enzyme Prodrug Therapy (CDEPT). Previous iterations of this system incorporated a nitroreductase gene, used for the breakdown of the prodrug CB1954. During this project alternative prodrugs were investigated, in this case carboxypeptidase G2. Alternatives into the prodrug and enzyme system are also being investigated in a direct action therapy in the form of the monoclonal anti-VEGF. The aims of this project were to implement the genes and optimise the activity of the drugs if necessary. It was also necessary to confirm that the bacterium was a non-pathogenic group 1 bacterium through sequencing and annotation of the genome.